Metadata Arsip Audio Berbasis Aplikasi Sederhana Perkantoran Di Museum Musik Indonesia - Rizky, Abrari Thoriq; Pradana, Kristoforus Raditya; Purnomo, Muhamad Ilham (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The aim of this research is to design an audio archive metadata application using Microsoft Access for the rock music collection at the Indonesian Music Museum, Malang City. The type of research is descriptive with a qualitative approach, where the data used in the research is primary data, namely the results of interviews with the management of the Indonesian Music Museum to obtain data about the number, type and variety of rock music collections in audio form with CD and vinyl storage media. Secondary data was also used in this research, namely in the form of documents and reports that were successfully stored to add information to the primary data. The result of carrying out this research is the design of an audio archive storage system for music collections with the rock genre at the Indonesian Music Museum. The design of this storage system begins by producing a rock music collection classification list, where the function of this classification list is to provide code and make it easier to input data in Microsoft Access. The design that has been successfully created makes it easy for the management of the Indonesian Music Museum to store music collections, especially those in the rock genre, if this collection experiences additions at a later date and makes it easier to retrieve information if information is needed.